Changing epidemiological characteristics of Hepatitis A and warning of Anti-HAV immunity in Beijing, China: a comparison of prevalence from 1990 to 2017 - Huai Wang; Pei Gao; Weixin Chen; Shuang Bai; Min Lv; Wenyan Ji; Xinghuo Pang; Jiang Wu (Taylor & Francis Group, 2019)
Backgroud: Beijing was hyper-endemic for hepatitis A until the 1990s and has been vaccinating against hepatitis A since 1994. The objective is to study the epidemiology and changes of antibody level of hepatitis A from 1990 to 2017. Methods: A multistage randomized cluster sampling serological cross-sectional study was conducted in individuals over one year old in 1992, 2006 and 2014 in Beijing. Venous blood samples were collected to test anti-HAV antibody. The incidence data of hepatitis A were obtained from National Notifiable Disease Reporting System (NNDRS) and CDC statistics in Beijing. The vaccination data of hepatitis A immunization were acquired from Beijing Immune Information System. Results: From 1990 to 2017, the reported incidence rate of HAV in Beijing declined from 59.41/100,000 in 1990 to 0.80/100,000 in 2017. The average age of HAV infection was postponed from individuals under 20 years old to individuals over 20 years old. After hepatitis A vaccine was introduced to Beijing, the outbreak of hepatitis A decreased sharply. Adjusted anti-HAV positive rate in general population was 68.23%, 81.73% and 82.47% respectively in 1992, 2006 and 2014. Due to hepatitis A vaccination conducted in children, the anti-HAV positive rate in individuals under 20 years old increased from 1992 to 2014, while in individuals over 20, this rate was barely changed. The coverage rate in target population was higher than 99% after hepatitis A vaccine was integrated into Expanded Program on Immunization (EPI). Conclusion: Incidence rate of hepatitis A in Beijing has decreased dramatically from 1990 to 2017. Hepatitis A vaccine plays an important role in protecting individuals under 20 years old. A higher proportion of adults will be susceptible to hepatitis A virus due to the decay of antibodies as they grow up from childhood to adulthood, which may result in possible outbreak of hepatitis A.